The Plain Man's Pathways to Heaven: Kinds of Christianity in Post-Reformation England, 1570-1640 - Murray, Derek B. (Implicit religion, 2010)
The article reviews the book "The Plain Man's Pathways to Heaven: Kinds of Christianity in Post-Reformation England, 1570-1640," by Christopher Haigh.